The Influence of Competence and Transformational Leadership on Auditor Performance: The Mediating Role of Organizational Commitment Using SEM (Structural Equation Modeling) - Iqbal, Mohamad; Winarningsih, Srihadi; Mubarrok, Ahmad Zakie (Universitas Muhammadiyah Pontianak, 2025)
This study examines the influence of competence and transformational leadership on the performance of internal auditors in the public sector, with organizational commitment as a mediating variable. Focusing on auditors at Indonesia’s Financial and Development Supervisory Agency (BPKP), the research addresses persistent challenges in audit effectiveness, including uneven competence levels and leadership dynamics within a bureaucratic structure. Using a quantitative approach and Structural Equation Modeling (SEM) with AMOS, data were collected via a structured questionnaire distributed nationwide. The results indicate that both competence and transformational leadership have significant positive effects on organizational commitment. Competence emerges as the strongest predictor of auditor performance, both directly and indirectly through commitment. Transformational leadership does not significantly affect performance directly but exerts a meaningful indirect influence via organizational commitment. These findings underscore the critical role of auditor competence and the importance of fostering commitment to enhance public sector audit effectiveness.